China’s Research Funding for the Humanities and Social Scienc - Yang, Rui; Lin, Yujie (International Higher Education, 2025)
<h3 id="designed-to-align-research-with-national-priorities-chinas-dual-track-funding-system-for-the-humanities-and-social-sciences-hss-comprises-both-vertical-government-led-and-horizontal-stakeholder-driven-channels-despite-substantial-growth-in-national-rd-investment-hss-research-continues-to-lag-behind-stem-research-due-to-policy-driven-funding-imbalances-systemic-challenges-including-the-entrenched-role-of-guanxi-rigid-performance-based-evaluation-frameworks-and-unequal-resource-distribution-undermine-equity-and-constrain-the-innovative-potential-of-hss-disciplines" data-pm-slice="1 1 []">Designed to align research with national priorities, China’s dual-track funding system for the humanities and social sciences (HSS) comprises both vertical (government-led) and horizontal (stakeholder-driven) channels. Despite substantial growth in national R&D investment, HSS research continues to lag behind STEM research, due to policy-driven funding imbalances. Systemic challenges, including the entrenched role of guanxi, rigid performance-based evaluation frameworks, and unequal resource distribution, undermine equity and constrain the innovative potential of HSS disciplines.